The analysis of telephone consultation contents of patients with bipolar disorder received by a self‐help group. Issue 2 (23rd June 2022) - Isogaya, Yuko; Suzuki, Chiho; Hoshina, Shingo; Nibuya, Masashi; Suzuki, Eiji
Abstract: Aim: Previous research shows that telephone consultation is useful in suicide prevention, substance use disorder, and other mental illnesses. However, no study has been conducted with a specific focus on telephone consultation for patients with bipolar disorder (BPD). Therefore, this study investigates the utilization of telephone consultation by patients with BPD and their families and analyzes the consultation contents to identify specific issues that they face. Methods: We investigated a record book of telephone consultation conducted between 2013 and 2019 provided by the Japanese Alliance of Bipolar Disorder, which is a self‐help group in Japan specializing in BPD. The main themes regarding consultation were extracted and labelled as diagnosis, symptoms, treatment, laws and social support, interpersonal relations, social life, other people with BPD, and others, with up to three items being labeled per consultation. Results: A total of 3540 consultations were sought, and consulters who were patients accounted for 74% of the calls. The largest number of consultations were those related to symptoms (1522), followed by interpersonal relations (1003), social life (896), and treatment (797). There was a significant difference in the distribution of consultation contents between patients and their families ( χ 2  = 44.595, p  < 0.0001). Conclusion: Most consultations by patients with BPD were about their psychiatric symptoms. Consultation contents differed between patients and families, with patients focusing more on their own social life and families focusing more on the treatment of BPD. These findings could help health‐care professionals in formulating effective psychoeducation and psychotherapy programs. Abstract :